Nursing Intervention to Reduce Anxiety of Acute Coronary Syndrome Patients Undergoing Cardiac Catheterization: Literature Review - Andri Febriansyah; Ni Luh Widani (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2024)
Background : Cardiac catheterization is the procedure of inserting a catheter into the heart through an artery or vein. Before undergoing a cardiac catheterization procedure, patients may experience anxiety, which can impact the heart's physiological response and heart health, as well as increase the risk of cardiovascular disease. Objective: Determine how effective Benson's relaxation techniques and educational videos are in reducing anxiety in patients undergoing cardiac catheterization. Method: The PICO structure was used as a guide to search the literature on anxiety reduction. The population under considered is individuals who experience anxiety. The interventions studied were Benson's use of video education and relaxation techniques. The searches were conducted between 2019 and 2023, through databases such as ProQuest, PubMed, Scholar, and Sciencedirect. Results: Of the 5,045 articles found, only 12 met the criteria and were assessed. The results of the study showed that the use of educational videos was successful in reducing anxiety levels in patients before undergoing cardiac catheterization procedures. In addition, Benson's relaxation technique has also been shown to help reduce anxiety in patients undergoing the same procedure. Conclusion: The Benson relaxation method was successful in increasing patient comfort and reducing anxiety, but educational videos can be a useful alternative.